Superconductivity and superionicity in doped rare-earth metal hydrides: Insights from first-principle calculations - Zifan Wang; Heejung Kim; Ji Hoon Shim; Duck Young Kim (Computational Materials Today)
Hydrides have attracted elemental attention due to their potential for high-temperature superconductivity under pressure, with recent discoveries pushing the boundaries of this field. In this study, we systematically investigated the superconducting and superionic properties of rare-earth metal hydrides with Fm3̅m symmetry, doped with carbon and nitrogen. By introducing highly electronegative elements at the tetrahedral sites or octahedral sites, we explored the effects of doping and hydrogen vacancies. Using first-principles calculations, we identified several metastable structures at ambient pressure with superconducting transition temperatures (Tc) reaching up to 14 K. Additionally, ab initio molecular dynamics simulations revealed superionic behavior, which coexists with superconductivity in these compounds. The electride nature of pure rare-earth metals plays a crucial role in driving superconductivity at low temperatures and enabling the transition to superionicity at higher temperatures. Our results highlight the potential of rare-earth metal hydrides as a novel class of superconductors, exhibiting both superconductivity and superionicity, with intriguing implications for future materials design.